Chemical and morphological variations of Czech and Finnish Acorus calamus L. accessions in gene bank collections - Dusek, Karol; Galambosi, Bertalan; Hethelyi, Eeva B; Kornel, Karoly; Karlova, Katarina (MTT, 2008)
Sweet-flag (Acorus calamus L., Araceae) is an aromatic perennial herb. Its dried roots have long been used in medicinal preparations and for the flavouring of bitter liqueurs and appetizers. Due to the habitat loss of Acorus its populations have become rare in several European countries. The focus now is on the conservation of its genetic resources and to start its field cultivation to meet the raw material demand. The aim of this study was to analyse the chemical and morphological characters of Acorus calamus collected from the nature in Finland - before deposit to the Nordic Gene Bank - and to compare them to the Acorus accessions collected in the Czech Gene Bank. The Finnish accessions have been collected during 2002 in South-West Finland at seven natural populations. One accession was obtained from Slovenia (Zalec) and their cuttings were transplanted into the field (moisture sandy till, pH 6.8) of Agrifood Research Finland, Mikkeli. The collection of Czech sweet-flags has been found in 1998 and it consists from 27 accessories originated from all country. The cuttings were replanted into the growing containers to Gene Bank in Olomouc, where a special basin was built to keep them in optimal wet conditions and to protect sprouting of rhizomes and mixing. Leave and rhizome morphological characters, essential oil content and composition of the dried rhizome were determined (Czech accessions during 1997 2000, Finnish accessions during 2004). The average oil content of the Finnish and Slovenian accessions was 1.47% (1.15 - 1.87%) and the oil composition was quite similar. Their main compounds were solavetivon (x = 11.07 %) and beta asarone (10.08%). The Czech accessions had a similar essential oil content and composition as the Finnish and Slovenian origin ones. The average essential oil content of 1.91% (1.20% 2.92%) is slightly higher than in Finland, but anyway 14 from 24 analysed samples did not execute the norm defined for quality of Radix calami (minimum 2% of essential oil) by Czech Pharmaceutical Codex. The main components of the essential oils were beta- and gamma- asarones. The average content of gamma-asarone was 18.65% (12.52 25.35%) and that of the beta-asarone was 16.11% (11.34 21.30%). The content of the beta-asarone in sweet-flag drug did not exceed the maximal recommended value 0.5% of dry matter content. The Finnish, Slovenian and Czech origin sweet-flags in both Finnish and Czech collections seemed to be phenotypically and chemically very similar to each other. They all represent the European triploid type of Acorus calamus var. calamus. The average essential oil content (1.47% in Finland and 1.91% in the Czech Republic) is not sufficient according to the Czech norm for Radix calami quality, but the content of carcinogen beta-asarone did not exceeded secure limit 0.5% of dry drug mass.
Keywords: Pu; plant genetic resources; Acorus; sweet-flag